PSYCHOLOGICAL THEORIES ABOUT THINKING IN PRESCHOOL CHILDREN - Ilhomjon Sobirovich Soliyev; Nozimakhon Qakhramonjon qizi Qodirova (Modern American Journals, 2025)
This article analyzes the main psychological theories that explain the development of thinking in preschool children. Based on the views of Piaget, Vygotsky and other scientists, children's logical thinking, imagination and problem-solving abilities are gradually revealed. The theories are compared and their practical significance is highlighted.
Keywords: Thinking, preschool age, cognitive development, Piaget's theory, Vygotsky, sociocultural approach, child psychology, play, speech, communication.